Pengaruh Gaya Belajar, Kemandirin Belajar Dan Kecerdasan Emosional Terhadap Prestasi Belajar Mata Pelajaran Ekonomi - Vani Agista Mahalia; Edi Fitriana Afriza; Gugum Gumilar (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The research problem concerns low student achievement. The objective is to determine the influence of learning styles, learning independence, and emotional intelligence on student achievement, both partially and simultaneously. The method used was a survey. The population in this study were students at MA Al Ittihad Sidareja. The sampling technique used was a saturated sampling method. In this study, data collection was conducted using a questionnaire, and the data analysis technique used was multiple linear regression analysis. The results indicate a positive and significant influence between learning styles, learning independence, and emotional intelligence on student achievement, both using the t-test (partial) and the f-test (simultaneous). This study is expected to provide an understanding of the importance of learning styles, learning independence, and emotional intelligence in improving learning achievement, as well as strategies that can be applied to develop these three factors in the learning context.